Working with indigenous knowledge : a guide for researchers - Grenier, Louise (International Development Research Centre, 1998)
Experience has shown us that development efforts that ignore local technologies, local systems of knowledge, and the local environment generally fail to achieve their desired objectives. Examples abound of western-lead teams of researchers failing to consult properly with indigenous populations, with the resulting "advancements" quickly proving to be unsustainable or, tragically, destructive. Thankfully, this trend is slowly changing. In the 1990s, indigenous knowledge has been fertile ground for research, and a wealth of information now exists on the topic. The information, however, is disparat